Analysis Of The Interaction Between Marketing Communication Strategies And Economic Factors In Consumer Decision Making: Integrating Microeconomic Perspective And Communication Theory - Pramesworo, Ignatius Septo; Alijoyo, Franciskus Antonius; Judijanto, Loso; Setianti, Yanti; Susanto, Hari (Universitas Dharma Wacana, 2024)
This paper examines the interaction between marketing communication strategies and economic factors in consumer decision-making, integrating insights from microeconomic perspectives and communication theory. Economic conditions influence consumer behavior, shaping preferences, perceptions, and purchasing decisions. Marketing communication strategies play a pivotal role in navigating these dynamics, encompassing tactics such as advertising, sales promotion, public relations, and personal selling. By understanding the interplay between economic factors such as price, income, and consumer preferences, businesses can develop targeted communication strategies that resonate with consumers and drive desired outcomes. This paper synthesizes vital theoretical perspectives from microeconomic and communication theories, exploring concepts such as price elasticity of demand, consumer preferences, and communication models. Through a review of empirical research and case studies, the paper illustrates how businesses adapt their marketing communication strategies to economic fluctuations and consumer behavior. By leveraging data analytics and prioritizing ethical considerations, businesses can effectively engage with consumers and achieve a competitive advantage in the marketplace.